Effectiveness Of Implementing Discipline Regulations In Improving The Performance Of Civil Servants In The Department Of Population And Civil Registration Cilegon City Government - Muhamad Arfan Amin; Muhammad Suparmoko; Wahyu Wiguna (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpose of this study is to evaluate how well the Department of Population and Civil Registration (Disdukcapil) of Cilegon City has implemented employee discipline policies. The research focuses on four aspects: the accuracy of regulation targets, the dissemination of disciplinary regulations, the objectives of discipline enforcement, and the monitoring of its implementation. The research method applied is descriptive qualitative, with data collected through interviews, observations, and documentation. The study involved 10 informants, consisting of structural officials and staff members directly involved in monitoring work discipline. The findings reveal that the implementation of disciplinary regulations has not been fully effective. First, the accuracy of the regulations is limited as most of them emphasize attendance rather than work quality. Second, the dissemination of disciplinary regulations remains insufficient and relies on conventional methods without utilizing digital technology. Third, the objectives of discipline regulations, which aim to improve compliance and performance, have not been fully achieved, as indicated by persistent lateness violations and a decline in program achievement rates. Fourth, the monitoring process is still inadequate, as supervision primarily focuses on attendance instead of productivity.This study concludes that the effectiveness of disciplinary regulation implementation is influenced by target accuracy, the intensity of dissemination, the consistency of supervision, and organizational culture. The study implies the need for technology-based dissemination strategies, consistent enforcement of sanctions, and real-time monitoring systems to enhance employee compliance.